1955
DOI: 10.1021/ja01626a068
|View full text |Cite
|
Sign up to set email alerts
|

The Acidity of Nitroguanylhydrazones

Abstract: Acidity of Nitroguanylhydrazones 5693 heated on a steam-bath for one-half hour. The solid, which separated, was removed, washed with ether and recrystallized from ethanol. Although the first crop of crystals was mainly collidine hydrobromide, concentration of the mother liquor followed by addition of ethyl acetate caused the separation of 75 mg. (21%) of yellow crystals, m.p. 206-212°, as expected for dehydroquinolizinium iodide. A sample of these crystals was converted to the corresponding picrate, m.p. 179-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1958
1958
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Reaction of N G with other secondary amines resulted in denitrosation (6). In the reaction of N G with azide ion the methylnitrosamino group is eliminated and 5-nitroaminotetrazole is formed by cyclization of the intermediate nitrogiianylazide (7). The reaction between MNTS and piperidine results in transfer of the nitroso group to form N-nitrosopiperidine without the formation of any diazomethane (4).…”
mentioning
confidence: 99%
“…Reaction of N G with other secondary amines resulted in denitrosation (6). In the reaction of N G with azide ion the methylnitrosamino group is eliminated and 5-nitroaminotetrazole is formed by cyclization of the intermediate nitrogiianylazide (7). The reaction between MNTS and piperidine results in transfer of the nitroso group to form N-nitrosopiperidine without the formation of any diazomethane (4).…”
mentioning
confidence: 99%
“…Upon treatment of II with the corresponding alkyl or aryl halide at room temperature, a solid powder was obtained after recrystallization. On the basis of the spectral and analytical data, it was found that in the product, the alkyl or aryl groups were connected to the secondary amine (−NH−) rather than the less sterically hindered primary amine (−NH 2 ) . A simple calculation was used to determine the heat of anion formation.…”
Section: Resultsmentioning
confidence: 99%
“…Bacarella, Grunwald, Marshall, and Purlee (5) determined the pK" values of formic, acetic, propionic, and benzoic acids and for V-methyl-and V,V-dimethylnnilinium ions in methanol-water containing from 0 to 95% methanol. Henry, De Vries, and Bosch an (87) spectrophotometrically determined the acid dissociation constant, pKa, of the follow- Martin (160) observed that peracids are stronger than the parent acid by about 3.5 pK" units; hydroperoxides behave as very weak acids with pK" values of 11.6 to 12.8. The acid strength of a peroxide is greater when the peroxide is linked to a primary rather than to a secondary carbon.…”
Section: Strengths Of Acids and Basesmentioning
confidence: 99%